PERSEPSI KEMUDAHAN, RESIKO DAN KEPERCAYAAN TERHADAP KEPUTUSAN PENGGUNAAN GOPAY - Buyung Nova Tri Anggono; Istiatin Istiatin; Solichul Hadi A B (STIE Pelita Nusantara Semarang, 2020)
The aims of this study is to determine and explain the simultaneous and partial influence of perceptions of ease, risk and trust in the decision to use Gopay. The research method of this study was quantitative descriptive method. The population is all active student of Batik Islamic Surakarta University. The number of sample was determined by using Slovin formula which has result of 100 respondents. The sampling technique was using purposive sampling method meanwhile questionnaire was used to collect the data. The technique of the data analysis used in this study are the classical assumption test instrument and hypothesis test (multiple linear regression analysis, F test, t test and coefficient of determination) with the help of SPSS Statistics. The results of this study shows that the variable perception of ease, risk and trust affect the decision to use Gopay. The t-test results shows the perception of ease affect the decision to use Gopay. The risk does not affect the decision to use Gopay. Trust influences the decision to use Gopay. Suggestions from this research are Gopay should increase its convenience, reduce risk, and maintain credibility so that consumers will continue to trust Gopay